Preliminaries to Programming a Computer for Psychiatric Diagnosis - Dale, P. W. (Methods of Information in Medicine, 1964)
A digital computer can be programmed to first detect commonly recurring symptom groups — diagnostic categories — and can measure the degree of fit of any new case to these computer determined diagnostic categories. The method is a Boolean logic system which should add precision in psychiatric diagnosis and research.Ein digitaler Computer kann so programmiert werden, daß er zunächst häufig—auftretende Symptomengruppen — diagnostische Kategorien — auffindet und gleichzeitig angibt, inwieweit ein neuer Fall in diese diagnostischen Kategorien paßt. Die Methode beruht auf einem Booleschen System, dessen Anwendung auf dem Gebiet der psychiatrischen Diagnostik und Forschung zu einer größeren Präzision führen könnte.